The minimum metallicity of globular clusters and its physical origin - implications for the galaxy mass-metallicity relation and observations of proto-globular clusters at high redshift - Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society. Letters, 2019)
ABSTRACT. In the local Universe, globular clusters (GCs) with metallicities [Fe/H] < −2.5 are extremely rare. In this Letter, the close connection between G